Harnessing Pseudomonas spp. for sustainable plant crop protection - Alattas, Hussain; Glick, Bernard R.; Murphy, Daniel V.; Scott, Colin (Frontiers in Microbiology, 2024)
This review examines the role of Pseudomonas spp. bacteria as biocontrol agents against crop diseases, focusing on their mechanisms of action, efficacy, and potential applications in sustainable agriculture. Pseudomonas spp., ubiquitous in soil ecosystems and root microbiomes, have attracted attention for their ability to suppress phytopathogens and enhance plant health through various mechanisms. These include direct competition for nutrients, production of antimicrobial compounds and volatile organic compounds, competition using type VI secretion systems, and indirect induction of systemic resistance. Our review shows that Pseudomonas strains effectively control a wide range of diseases across diverse plant species, with some strains demonstrating efficacy comparable to chemical fungicides. However, the review also highlights challenges in achieving consistent performance when using Pseudomonas inoculants under field conditions due to various biotic and abiotic factors. Strategies to optimize biocontrol potential, such as formulation techniques, application methods, and integration with other management practices, are discussed. The advantages of Pseudomonas-based biocontrol for sustainable agriculture include reduced reliance on chemical pesticides, enhanced crop productivity, and improved environmental sustainability. Future research directions should focus on understanding the complex interactions within the plant microbiome, optimizing delivery systems, and addressing regulatory hurdles for commercial deployment. This review underscores the significant potential of Pseudomonas spp. in sustainable crop protection while acknowledging the need for further research to fully harness their capabilities in agricultural systems.